Social Psychology / Fourth Edition - Hogg Michael A; Vaughan Graham M (Pearson - Prentice Hall, 2005)
This book provides an accessible and stimulating introduction to the field. Fully revised and updated to reflect recent research, it consolidates European and North American perspectives to provide coverage of social psychology that meets the needs of undergraduate students. Preface, Publisher's Acknowledgements, Guided Tour, Web Tour, Introducing Social Psychology, Social Cognition and Social Thinking, Attribution and Social Knowledge, Self and Identity, Attitudes, Persuasion and Attitude Change, Social Influence, People in Groups, Leadership and Decision Making, Prejudice and Discrimination, Intergroup Behavior, Aggression, Affiliation and Attraction and Love, Prosocial Behavior, Language and Communication, Culture, Glossary, References, Author and Subject Index.